Caregivers’ burden and other selected problems of patients treated for heart failure - Białek, Katarzyna; Sadowski, Marcin (Medical Studies/Studia Medyczne, 2019)
Heart failure is a rapidly growing health concern affecting nearly 800 thousand patients in Poland. Heart failure is the primary reason for hospitalisation after 65 years of age. And although most research focuses on the treatment and functioning of patients, life with heart failure is usually a shared experience and has a significant impact on the quality of life of other family members, and there are considerable implications for caregiver well-being. Research has shown that caregivers of patients with heart failure reported similar problems to the caregivers of patients with other chronic diseases; these included physical exhaustion, high stress, depressive and anxiety disorders, and reduced quality of life. The aim of this review is to summarise the needs and psychological reactions of caregivers of patients treated for heart failure, and an assessment of factors that affect the burden of caregivers and reduce their quality of life.